ENHANCING BILLBOARD TAX IMPLEMENTATION FOR MAXIMUM REVENUE STREAMS - Karim, Alifzonardi Rahman; Aneta, Yanti; Tui, Fenti Prihatini (Public Policy Journal, 2023)
This research aims to find out (1) the implementation process of the billboard tax collection policy in Gorontalo City, and (2) the factors determining the success of the billboard tax collection policy in Gorontalo City. This research uses a descriptive qualitative method by using data sources conducted through in-depth interviews with informants. The research findings show that the Implementation Process of the Reclame Tax Collection Policy in Gorontalo City is good in planning, implementation, monitoring, and evaluation. In general, it has been implemented but is not optimal. In the implementation stage, it has not been optimal in terms of annual realization revenue. In the monitoring and evaluation stage, has been through meetings but has not shown the suitability between the implementer's achievements and what was targeted in the planning. Factors that determine the success of the Implementation of the Billboard Tax Collection Policy in Gorontalo City communication, the attitude of implementers, and the bureaucratic structure have been implemented well. As for resources, they have limited human resources.